Factors affecting public housing credit choice of sharia property developer in Central Java - Nurzahroh Lailyah (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2020)
Purpose – This study analyses the various factors that affect the probability of consumers choosing public housing credit (PHC) of Sharia Property Developer (SPD) in Central Java.Method – The data of this study are primary data obtained through questionnaires to 252 people from a population of 1,269 PHC SPD consumers in Central Java (Boyolali Regency, Magelang Regency, Pati Regency, Semarang City, and Wonosobo Regency). Furthermore, consumer data were analysed using a binary logit regression model with SPSS software.Result – The results of this study state that the variable price and religiosity have a significant negative effect on the probability of choosing a PHC in Islamic Property Developer. In comparison, the variables of income, location, and facilities do not significantly affect the likelihood of selecting a PHC on a Sharia Property Developer. Wonosobo Regency is the region with the most significant probability of choosing a PHC on a Sharia Property Developer compared to Boyolali, Pati, Magelang, and Semarang City Regencies. Meanwhile, Pati Regency is the region with the least probability of choosing a PHC as a Sharia Property Developer. Implication – The Central Java SPD can use the finding of this research to consider the evaluation and improvement of PHC products in the future. So that consumers do not turn to competitors, have more confidence, and are satisfied with Sharia Property Developer services.Originality – The originality of this research lies in the object under study, test analysis, and research location.